MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN DARING IPA BERBANTUAN MEDIA QUIZIZ - Maryani Maryani; Andriana Marsianti (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This study aims to increase student learning activity in online science learning with the help of quiziz educational media. This research is classroom action research with 32 students as the subject of class IXA UPTD SMP Negeri 1 Merawang. This research was carried out in 2 cycles, each cycle having 2 meetings. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The implementation of the research stages is adjusted to the online learning mode. The data collection instrument was an observation sheet on the implementation of the online learning process assisted by the quiziz educational media, while the data analysis technique used quantitative and qualitative descriptive analysis techniques using achievement criteria. The benchmark for the success of this research is that 80% of the 32 students have reached the criteria for activeness. Based on the results of the study, in the first cycle of the 1st meeting, 43.8% of active students were found in the low category. The second meeting of students who have been active as much as 65% (enough category). Meanwhile, in the second cycle of the 1st meeting, 65.6% of active students were found in the sufficient category. At the 2nd meeting, it increased to 81.3% (high category). So from cycle I and cycle II there was an increase in student activity of 19.5%. The research can be concluded that quiziz educational media can increase student activity in online science learning in class IXA UPTD SMP Negeri 1 Merawang.